Multi-objective optimisation of a honeycomb-filled composite energy absorber for subway vehicles. Issue 6 (1st November 2020) - Xu, Ping; Zhao, Hui; Yao, Shuguang; Che, Quanwei; Xing, Jie; Huang, Qi; Xu, Kai
Abstract: To meet the requirements of passive safety protection during vehicle collision, a honeycomb-filled composite energy absorber (HFCEA) was designed in this study. A finite element model was established and effectively verified using experimental data. To evaluate the effects of the outer tube thickness, diaphragm thickness and honeycomb strength on the specific energy absorption (SEA) and the undulation of the plateau force (UPF), a polynomial response surface method was employed. To optimise the crash performance of the structure, i.e. to maximise the SEA and minimise the UPF, a multi-objective particle swarm optimisation was performed. A critical honeycomb strength was determined, beyond which the composite structure loses its weight efficiency. The UPF could be significantly reduced by increasing the honeycomb strength and reducing the outer tube thickness. This shows that the proposed composite structure can serve as an excellent crashworthy device for railway vehicles.